Dietary Consumption Patterns and Their Predictors Among Young Children in Northern Ghana. (7th June 2021) - Becher, Emily; Davis, Jennie; Kumordzie, Sika; Wessells, K. Ryan; Arnold, Charles; Tan, Xiuping; Adu-Afarwuah, Seth; Haskell, Marjorie; Adams, Katherine; Vosti, Stephen; Engle-Stone, Reina
Abstract: Objectives: To assess the prevalence and frequency of consumption of vegetables, fruits, sugar sweetened beverages (SSBs), salty and sweet snacks and the relationship between consumption and household characteristics (residence location, food insecurity, and socioeconomic status [SES]) among children 2–5 years of age in two districts in the Northern region of Ghana. Methods: Households were recruited from 14 urban, 8 semi-urban and 6 rural clusters in the Tolon and Kumbungu districts in Northern Ghana. Primary caregivers of children 2–5 years (n = 242) reported the number of days in a typical week selected food items were consumed, and the number of servings per day. Household characteristics, food insecurity (USAID Household Food Insecurity Access Scale) and SES, were assessed via questionnaires administered to the head of household. We examined the relationships between consumption of each food and 1) residence (urban vs. semi-urban/rural), 2) household food insecurity (moderate/severe vs. none/mild) and 3) household SES (lowest quartile vs. other quartiles). Results: The proportion of children who consumed each food in a typical week was: 98% vegetables, 81% sweet snacks, and 75% fruits; approximately half of children consumed salty snacks (51%) or SSBs (46%). Mean (SD) servings consumed in a typical week were: 7.85 (7.32) vegetables, 2.82 (2.51) sweet snacks, 2.54 (3.69) SSBs, 1.77 (1.70) fruits, and 1.17 (1.67) salty snacks. Consumption of fruits (82% vs 68%, p = 0.01) and sweet snacks (91% vs 71%, p < 0.0001) was more common in urban areas than in rural areas, but consumption of vegetables, salty snacks, and SSBs was not associated with residence location. Household food insecurity and SES were not associated with consumption of any of the foods examined. Conclusions: Although quantitative intake data were not available, these data suggest that, on average fruit and vegetable intake may be low relative to Ghana Dietary and Physical Activity Guidelines for daily servings, while SSBs and sweetened snacks are common. Eating patterns among young children may differ between urban and rural environments within these two districts. Funding Sources: Funding was provided to UC Davis from Helen Keller International.